Sistem Pendukung Keputusan Dengan Metode Weighted Product Untuk Memilih Protokol Pengobatan Pneumonia Pada Anak Berdasarkan Kondisi Klinis - Nurmala Sridewi; Dewi Wahyuni (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2025)
Pneumonia is one of the leading causes of morbidity and mortality in children, especially in developing countries. Choosing the appropriate treatment protocol is crucial to ensure the effectiveness of therapy and prevent complications. This study develops a Decision Support System (DSS) using the Weighted Product (WP) method to assist healthcare professionals in determining the appropriate pneumonia treatment protocol for children based on clinical conditions. The system takes into account various criteria, such as the severity of pneumonia, patient age, nutritional status, the presence of comorbidities, and the response to initial treatment. The test results show that this system can provide accurate and consistent recommendations in accordance with current clinical guidelines. Therefore, this DSS can be an effective tool to improve the quality of clinical decision-making. Keywords: Decision Support System, Weighted Product, Pneumonia, Children, Treatment Protocol, Clinical Conditions.